Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T19:51:11+01:00
A)
0,3x+0,4y=79
0,3(x+y)=66

0,3x+0,4y=79
0,3X+0,3Y=66/:0,3

0,3x+0,4y=79
x+y=220

0,3x+0,4y=79
x=220-y

0,3(220-y)+0,4y=79
x=220-y

66-0,3y+0,4y=79
x=220-y

0,1y=13/:0,1
x=220-y

y=130
x=220-130

y=130
x=90

b)
0,9x=y+3
1,1y+6=x

y=0,9x-3
1,1(0,9x-3)+6=x

y=0,9x-3
0,99x-3,3+6=x

y=0,9x-3
-0,01x=-2,7/:-0,01

y=0,9x-3
x=270

y=0,9*270-3
x=270

y=240
x=270

1 5 1
2010-02-16T19:52:48+01:00
A)0,3x+0,4y=79
0,3(x+y)=66 stąd x+y=66/0,3 do rozwiązania x=66/0,3-y

0,3x+0,4y=79
0,3x+0,3y=66

0,3x+0,4y=79
-0,3x-0,3y=-66

0,1y=13
y=130

x=66/0,3-y=220-130=90

b)
0,9x=y+3
1,1y+6=x

0,9x-y=3
-x+1,1y=-6 mnożymy obustronnie przez 0,9

0,9x-y=3
-0,9x+0,99y=-5,4

-0,01y=-2,4 dzielimy obustronnie przez -0,01
y=240

x=1,1*240+6=270
1 5 1
2010-02-16T19:55:16+01:00
A)0,3x+0,4y=79
0,3(x+y)=66
0,3x+0,4y=79
0,3x+0,3y=66
-0,3x-0,4y=-79
0,3x+0,3y=66
-0,1y=-13
y=130
0,3x+o,4*130=79
0,3x+52=79
0,3x=27
x=90


b)0,9x=y+3
1,1y+6=x
0,9x-y=3
1,1y=X-6
0,9x-y=3
1,1y-x=-6
0,99x-1,1y=3,3
1,1y-x=-6
-0,01x=-2,7
x=270
0,9*270-y=3
243-y=3
-y=-240
y=240
1 5 1